2019
DOI: 10.1021/acs.jmedchem.8b01328
|View full text |Cite|
|
Sign up to set email alerts
|

Structure-Based in Silico Screening Identifies a Potent Ebolavirus Inhibitor from a Traditional Chinese Medicine Library

Abstract: Potent Ebolavirus (EBOV) inhibitors will help to curtail outbreaks such as that which occurred in 2014–16 in West Africa. EBOV has on its surface a single glycoprotein (GP) critical for viral entry and membrane fusion. Recent high-resolution complexes of EBOV GP with a variety of approved drugs revealed that binding to a common cavity prevented fusion of the virus and endosomal membranes, inhibiting virus infection. We performed docking experiments, screening a database of natural compounds to identify those l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…1A, right). Even in the high-resolution GP∆muc structures (66,72,73), the HR2 stalk still contains less helical content than most coiled-coils in the Protein Data Bank (PDB), ~15 aa vs ~30 aa, and becomes less regular and unwound towards the C terminus, suggesting an inherent instability in HR2 (Fig. 1D, left).…”
Section: Effect Of the Hr2 Stalk On Ebov Gp Metastability 127mentioning
confidence: 99%
See 1 more Smart Citation
“…1A, right). Even in the high-resolution GP∆muc structures (66,72,73), the HR2 stalk still contains less helical content than most coiled-coils in the Protein Data Bank (PDB), ~15 aa vs ~30 aa, and becomes less regular and unwound towards the C terminus, suggesting an inherent instability in HR2 (Fig. 1D, left).…”
Section: Effect Of the Hr2 Stalk On Ebov Gp Metastability 127mentioning
confidence: 99%
“…Corning). Based on recent studies on EBOV infectivity in various cell lines(72, 105), HEK293T cells or TZM-bl cells were used for ebolavirus-pp neutralization assays. Briefly, HEK293T cells or TZM-bl cells at 1×104 were added to each well and the plate was incubated at 37°C for 48 h.After incubation, overlying media was removed, and cells were lysed.…”
mentioning
confidence: 99%
“…Among the SERMs known to inhibit EBOV entry, only toremifene has been tested for its effect on GP stability (32)(33)(34)57). Here, we tested two additional SERMs and structural analogs of toremifene-clomifene and ospemifene.…”
Section: Serm-mediated Gp Destabilization and Inhibition Of Ebov Infementioning
confidence: 99%
“…Experimental studies around the Ebolavirus disease, both fundamental and clinical, have been reported extensively in recent years . For instance, a set of Ebolavirus GP experimental structures were reported [14][15][16][115][116][117], including both apo (unliganded) structure of Ebolavirus GP, and also high-resolution complex structures of GP with a series of directly interacting compounds (including a variety of approved drugs) and also its neutralizing antibodies (Tables 1 and 2).…”
Section: Motivationmentioning
confidence: 99%